2015
DOI: 10.3920/cep150027
|View full text |Cite
|
Sign up to set email alerts
|

Sweat facilitated losses of amino acids in Standardbred horses and the application of supplementation strategies to maintain condition during training

Abstract: Little is known about the amino acid composition of horse sweat, but significant fluid losses can occur during exercise with the potential to facilitate substantial nutrient losses. Sweat and plasma amino acid compositions for Standardbred horses were assessed to determine losses during a standardised training regime. Two cohorts of horses 2013 (n=5) and 2014 (n=6) were assessed to determine baseline levels of plasma and sweat amino acids. An amino acid supplement designed to counter losses in sweat during exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In a previous study, provision of a complex amino acid supplement to males from the general public resulted in reduced levels of fatigue [24] which provided some evidence that fatigue may be associated with a net deficit in the nitrogen balance. In another recent study investigating sweat losses in Standardbred horses during race training, provision of amino acids targeted to replace specific sweat-facilitated losses resulted in elevated resting plasma levels which could assist the support of high intensity training [25]. The athletes in the present study had resting plasma total levels of amino acids which were lower than general population literature values [26].…”
Section: Discussionmentioning
confidence: 70%
“…In a previous study, provision of a complex amino acid supplement to males from the general public resulted in reduced levels of fatigue [24] which provided some evidence that fatigue may be associated with a net deficit in the nitrogen balance. In another recent study investigating sweat losses in Standardbred horses during race training, provision of amino acids targeted to replace specific sweat-facilitated losses resulted in elevated resting plasma levels which could assist the support of high intensity training [25]. The athletes in the present study had resting plasma total levels of amino acids which were lower than general population literature values [26].…”
Section: Discussionmentioning
confidence: 70%
“…The cytoplasmic lysate was filtered by transferring to QIAgen spin columns and centrifuging at 15,000×g for 5 min. The filtered lysate (100 µL) was added to 200 µL Milli-Q H 2 O with 100 μL norvaline as the internal standard and processed using EZ:Faast™ (Phenomenex ® Inc.) derivatisation kits for amino acid analysis by gas chromatography with flame ionization detection (GC/FID) as previously described (Dunstan et al 2015). The EZ:Faast™ kit has been designed for rapid and efficient analyses of amino acids in plasma (Badawy 2019;Badawy et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…High levels of exercise activity would increase the requirement for protein intake and for protein turnover in order to offset the increased losses of free amino acids arising from demands for energy metabolism, tissue repair and recovery processes [8, 9] as well as excretory losses via sweating [10, 11]. Similar increased demands for amino acids would be seen during illness and recovery from trauma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the levels of several key amino acids including serine, glycine, histidine, alanine and ornithine are present in sweat at much higher concentrations than occur in the plasma [10, 11, 14, 15]. It was proposed that these levels of amino acids in sweat, as has been found to be the case with sweat electrolytes [16], could be achieved by a process of leaching of the amino acids from the natural moisturising factor in the stratum corneum of the skin to combine with the quantities excreted in sweat [10, 11, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation